THE RELATIONSHIP BETWEEN ENVIRONMENTAL FACTORS AND QUALITY OF LIFE OF TYPE 2 DIABETES MELLITUS - Kusuma, Abigail Sharon; Ismonah; Hartoyo, Mugi (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Type 2 diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia, which causes complications and affects quality of life. Environmental factors influence the quality of life of DM patients. This study aimed to determine the relationship between environmental factors and the quality of life of type 2 DM patients at the Manyaran Public Health Center, Semarang City. Method. This research was quantitative study with a cross-sectional approach. Sixty-three respondents were involved in this study, which was determined using a simple random sampling technique. The Perceived Neighborhood Environment questionnaire measures environmental factors, and DQOL measures quality of life. Result & Analysis. The analysis results showed that most respondents were >65 years old at 42.9%, 61.9% were female, and 38.1% had primary school as their last education. The analysis results also showed that most respondents have good environmental factors (98.4%) and a high quality of life (79.4%). Discussion. The results of the Spearman Rank test stated that there was a significant relationship between environmental factors and the quality of life of type 2 DM patients at the Manyaran Public Health Center (p-value 0.000), with the strength of moderate and positive (r = 0.467), where the better the environment, the higher the quality of life.